APP RETENTION (CIPEEX, 2022)
WITH THE ADVANCEMENT OF THE FIELD OF SCIENCE AND TECHNOLOGY, THE EXTREME RELATIONSHIP OFDEPENDENCE BETWEEN MAN AND THIS AREA, MADE THE HUMAN BEING DOOMED TO ALWAYS SEEK ANEW TECHNOLOGY. ONE OF THE AREAS THAT SUFFERED IMPACTS GENERATED BY THIS CONSTANT EVOLUTIONWAS EDUCATION, WHICH NEEDS TO CONSTANTLY ADAPT IN TERMS OF TECHNOLOGY. AT A GIVEN MOMENT,BOTH ELEMENTARY AND TECHNICAL EDUCATION UNDERWENT MOMENTS OF ADVANCES INDUCED BY THISTECHNOLOGICAL GROWTH. BECAUSE OF THIS, COLLEGE EDUCATION, ONE OF THOSE AFFECTED, IS HIT WITH APROBLEM THAT PLAGUES MOST INSTITUTIONS, WHICH IS THE DROPOUT OF STUDENTS DURING THE CURRENTPERIOD, DUE TO THE VOLATILITY OF SCIENTIFIC PROGRESS. IN ORDER TO ALLEVIATE THIS RECURRENCE, THE WORK AIMS TO BUILD A TOOL FOR THE GENERATION OF REPORTS, WHICH CAN HELP IN THE UNDERSTANDING AND REDUCTION OF THE IMPACTS THAT THE DROPOUT OF STUDENTS CAN CAUSE. TO INITIATE THE PROJECT, ABIBLIOGRAPHIC RESEARCH WAS CARRIED OUT IN THE AREAS OF EDUCATION, EVASION AND MACHINELEARNING TO BETTER UNDERSTAND THE SCOPE OF THE PROBLEM AND THE AREAS THAT SHOULD BE FOCUSEDON TO REACH THE BEST CONCLUSION. AT THE SAME TIME, ARTIFACTS WERE DEVELOPED TO INCREASE THEVERACITY OF THE SOLUTION, INCLUDING PM CANVA AND THE PRODUCTION METHODOLOGY FOR ORGANIZATION, PERSONAS, THE PRODUCT BACKLOG BUILDING TO PROVE REQUIREMENTS, IN ADDITION TO THE TEST PLAN, ARCHITECTURE AND STRUCTURING OF THE DATABASE. DATA, SO THAT THE DEMONSTRATION OF THE POSSIBILITY AND VIABILITY OF THE PRODUCT GENERATED DURING THE WORK WAS PALPABLE, SO THAT IT WAS POSSIBLE TO INTRODUCE THE IMPLEMENTATION OF THE ALGORITHM ON THE REAL DATABASE AND, THUS, ACCURATELY PRESENT THE POSSIBILITIES OF EVASIONS THROUGH SUCH REPORTS.
Keywords: Education; Evasion; College Education; Management Indicators; Software; Machine Learning